THE IMPORTANCE OF SPEED AND AGILITY IN TRAINING YOUNG VOLLEYBALL PLAYERS - Altinay Berdimuratova Konisbay kizi (American Journals Publishing, 2023)
The importance of physical qualities in the training of young volleyball players. The specific physical qualities of different sports differ from each other. Interrelationship of physical qualities of volleyball players.
Keywords: specifics - special structure, intensive - intensity.